2015
DOI: 10.1002/jsfa.7291
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmunised bovine milk and whey: influence of pH and enzymatic treatments on the antigen‐binding capacity of immunoglobulin G

Abstract: The ABC of IgG obtained from hyperimmunised bovine defatted milk and whey is largely reduced in conditions similar to those found in the human digestive tract. Only whole milk can maintain around 40% of their initial ABC. IgG encapsulation or other methods to protect the immunoglobulin activities could be an alternative to use these type of products in final foods formulae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Hemp extract has been shown to inhibit the proliferation and growth of prostate cancer (De Petrocellis et al., 2013) and melanoma (Blázquez et al., 2006)cells, and hemp derivatives are able to alter mitochondrial permeability of rat liver cells and increase cytochrome c release (Zaccagnino et al., 2012), suggesting that hemp peptides represent candidate anticancer agents. It has also been reported that the biological activities of peptides are modulated by molecular weight, with low molecular weight correlating with increased activity (Dugnol & Riera, 2016; Li et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hemp extract has been shown to inhibit the proliferation and growth of prostate cancer (De Petrocellis et al., 2013) and melanoma (Blázquez et al., 2006)cells, and hemp derivatives are able to alter mitochondrial permeability of rat liver cells and increase cytochrome c release (Zaccagnino et al., 2012), suggesting that hemp peptides represent candidate anticancer agents. It has also been reported that the biological activities of peptides are modulated by molecular weight, with low molecular weight correlating with increased activity (Dugnol & Riera, 2016; Li et al., 2019).…”
Section: Discussionmentioning
confidence: 99%